(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
One of the oldest instruments that is still in our people’s hands today is the rubob, and performance skills are getting better. It will be necessary to carefully master such a complex process as developing mature specialists for the future, continuing musical education in Instrumental Performance, teaching student-young students, the requirement to acquire theoretical and practical knowledge, learning Kashkar rubobi to form the skill of correctly positioning left-handed fingers, strengthening positions, and thorough mastery of bars in order to advance this process. This article provides insights and reflections on the structure of the Kashgar rhubarb and the musical performance in it.